2000
DOI: 10.1021/bi000700g
|View full text |Cite
|
Sign up to set email alerts
|

Proton Abstraction Reaction, Steady-State Kinetics, and Oxidation−Reduction Potential of Human Glutaryl-CoA Dehydrogenase

Abstract: Glutaryl-CoA dehydrogenase catalyzes the oxidation of glutaryl-CoA to crotonyl-CoA and CO(2) in the mitochondrial degradation of lysine, hydroxylysine, and tryptophan. We have characterized the human enzyme that was expressed in Escherichia coli. Anaerobic reduction of the enzyme with sodium dithionite or substrate yields no detectable semiquinone; however, like other acyl-CoA dehydrogenases, the human enzyme stabilizes an anionic semiquinone upon reduction of the complex between the enzyme and 2,3-enoyl-CoA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(93 citation statements)
references
References 51 publications
6
87
0
Order By: Relevance
“…Previous structural and enzymatic studies of GCDH have repeatedly demonstrated FAD to be a tightly bound cofactor for this enzyme. Human GCDH recombinantly expressed and purified in another laboratory by methods similar to those used here revealed FAD bound in the crystal structure, although FAD had not been explicitly added at any stage (Dwyer et al, 2000;Goodman et al, 1995;Fu et al, 2004). Biochemical efforts to remove FAD from Pseudomonas fluorescens GCDH in another laboratory required multiple acid-ammonium precipitation steps, generating a very unstable protein which lost all activity if FAD was not added back within minutes (Gomes et al, 1981).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous structural and enzymatic studies of GCDH have repeatedly demonstrated FAD to be a tightly bound cofactor for this enzyme. Human GCDH recombinantly expressed and purified in another laboratory by methods similar to those used here revealed FAD bound in the crystal structure, although FAD had not been explicitly added at any stage (Dwyer et al, 2000;Goodman et al, 1995;Fu et al, 2004). Biochemical efforts to remove FAD from Pseudomonas fluorescens GCDH in another laboratory required multiple acid-ammonium precipitation steps, generating a very unstable protein which lost all activity if FAD was not added back within minutes (Gomes et al, 1981).…”
Section: Discussionmentioning
confidence: 87%
“…Unlike other flavoproteins within this family, GCDH (EC 1.3.99.7) performs , -dehydrogenation as well as decarboxylation of its substrate glutaryl-CoA to yield the product crotonyl-CoA (Dwyer et al, 2000). Transfer of electrons from the glutaryl-CoA precursor to the electron-transfer flavoprotein is mediated by the cofactor flavin adenine dinucleotide (FAD) in both prokaryotic and eukaryotic electron-transport chains (Tsai & Saier, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The human enzyme has been studied extensively, and a number of mutations in the gene coding for human GDH have been identified, which have been associated with cerebral aciduria type I (21). Meanwhile, details about the structure-function relationship and the catalytic mechanism have been elucidated in studies with human GDH (14,16,34,35). A conserved catalytic glutamate residue abstracts the ␣-proton from the substrate, which is followed by hydride transfer from the ␤-carbon to the flavin cofactor.…”
mentioning
confidence: 99%
“…2). This arginine was expected to be involved in binding of the sulfino group of 3SP-CoA (1), in analogy to glutaryl-CoA dehydrogenases, where an arginine residue is involved in binding of the terminal carboxyl group (44)(45)(46)(47)(48) prior to decarboxylation. Three residues (E87, S95, and Y369, according to the numbering for human glutaryl-CoA dehydrogenase) which probably enable the decarboxylating reaction are absent from nondecarboxylating glutaryl-CoA dehydrogenases and from all 3SP-CoA desulfinases.…”
Section: Discussionmentioning
confidence: 99%